2010
DOI: 10.1002/adem.200900333
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity and Grain Boundary Diffusion at Small Grain Sizes

Abstract: Severe plastic deformation (SPD) processes have attracted considerable attention due to their potential for fabricating large quantities of material with an overall small grain size. [1,2] In the last decade, various SPD processes have been proposed for ultragrain refinement, such as high pressure torsion (HPT), [1] equal channel angular pressing (ECAP) [3] accumulative roll bonding (ARB) [4] or-for achieving the smallest grain sizes for pure metals through SPD-repeated cold rolling (RCR) [5,6] as attractive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 36 publications
(54 reference statements)
3
46
0
Order By: Relevance
“…In addition, recent studies showed that diffusion or segregation processes in ufg materials are considerably influenced by the highly-distorted non-equilibrium grain boundaries [65][66][67][68]. The vacancy-type free volumes are supposed to be mainly located in the grain boundary regions, thus enhancing grain boundary diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies showed that diffusion or segregation processes in ufg materials are considerably influenced by the highly-distorted non-equilibrium grain boundaries [65][66][67][68]. The vacancy-type free volumes are supposed to be mainly located in the grain boundary regions, thus enhancing grain boundary diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies demonstrated that transport properties of UFG materials (diffusion, segregation, etc.) are markedly affected by a so-called "nonequilibrium" grain boundary state [8][9][10]. At this place it is important to highlight that a broad spectrum of diffusivities of short-circuit paths is observed in UFG materials -contributions of high-angle grain boundaries with both "normal" and significantly enhanced diffusion rates can be differentiated in SPD-processed materials [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…2(a) was analyzed by the method of geometric phase analysis (GPA) that allows calculating relative magnitudes of the in-plane components of the strain tensor and of the tensor of rigid body rotation with respect to a reference lattice, based on the intensity distribution in high resolution electron micrographs [28,29]. Details concerning the analysis and concerning the conditions under which the HRTEM micrograph was taken can be found in [9]. One result of this analysis is displayed in Fig.…”
mentioning
confidence: 99%
“…And the geometric phase analysis was applied to determine the atomic level strains in high-resolution TEM (HRTEM) images, following the experimental process in Ref. [15]. Foils were mechanically thinned and electropolished in an electrolyte of 10 vol.% perchloric acid and 90 vol.% ethanol at −20°C.…”
Section: Methodsmentioning
confidence: 99%